GOLD FORMATIONS OF THE PRIAMURSKAYA PROVINCE - V. A. Stepanov; A. V. Melnikov (Известия высших учебных заведений: Геология и разведка, 2016)
It was found that within the Priamurskaya prov-nce of Late Me-ozoic age the depos-ts and occurrences of gold-quartz are wide-pread, and goldsulphide-quartz, goldsilver and goldpolymetallic formations are less popular. They all are the main producers of gold ore and determine the metahogenic specialization of the province. Deposits and oc-urrences of goldsulfide and goldcopper-mo-bdenum porphyry formations are less common, as well as goldskarn ore, goldmercury, gold and raremetal and goldantimony formations. It is shown that in the central part of the province deposits and occurrences of goldquartz are predominant, and on the periphery - the goldsulfide-quartz and goldsilver formations. Prospects for growth of the resource base of gold ore depostts are associated mainly with goldsulphide-quartz, goldquartz and goldsilver, to a lesser extent - with goldpolymetallic formation.